COVID-19 Outbreak and Industry Reactions: Evidence from Colombo Stock Exchange - Dissanayaka, Chiranthana Manohari; Anuradha, Niluka (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2022)
Moving along history, it can be identified that the human race has experienced many types of challenges which did have the capacity to decide human existence or extinction from the beginning. Some of these challenges were created by humans by themselves like world wars and some were created by natural forces like natural disasters and deadly viruses.Recently COVID-19 has taken place as a rapidly spreading virus by causing more than two million deaths and more than 95 million cases around the world as being the sixth global pandemic creating considerable influence to different industries such as agriculture, health and transportation in the world. The propose of this study is to identify the impact of COVID-19 on the performance of the industries in Sri Lanka. Using the two events and the event study methodology it is found that industry groups such as automobiles, materials, health care and equipment, household and personal care products are the significantly positively affected industries where industries like insurance and transportation have been negatively affected in Sri Lanka. As per the real business-cycle theory these fluctuations in the industries consider as business cycle fluctuations and the efficient response to exogenous changes in the real economic environment. Hence this impact does not last long, investors and the government can recover quickly with the implementation of effective monetary policies and investment diversifications